Single Stages Repair of Hypospadias Using The Snodgrass Technique: A Modern Choice - Karn, Binod; Shrestha, N. M. (Journal of Nepalgunj Medical College, 2018)
Background: Proximal hypospadias with chordee is the most challenging variant of hypospadias to reconstruct. During the last 10 years, the approach to severe hypospadias has been controversial. Materials & Methods: This is a hospital based observational study conducted in the plastic surgery unit of department of surgery at Nepalgunj Medical College and Teaching Hospital Kohalpur from 2012 March to 2016 September. All patients underwent single staged procedures using Snodgrass technique. Results: Thirty three patients were operated. Twenty four patients had no complications. Single fistula was present in 6(18.18%) patients. Two (6.06%) patients had 2 fistulae; one at the original site of the hypospadias and the other was sub-coronal. One (3.03%) patient had moderate meatal stenosis, which was successfully treated by repeated dilatations. Conclusion: Single Staged procedure using the principles of Snodgrass’s technique; is a versatile operation that can be used for the proximal hypospadias. It decreases the rate of fistula formation; disruption; stenosis and gives a satisfactory cosmetic appearance. JNGMC, Vol. 14 No. 2 December 2016, Page: 50-52